2022
DOI: 10.1101/2022.03.24.22272768
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Local CCL18 and CCL21 expand lung fibrovascular niches and recruit lymphocytes, leading to tertiary lymphoid structure formation in prolonged COVID-19

Abstract: Post-acute lung sequelae of COVID-19 are challenging many survivors across the world, yet the mechanisms behind are poorly understood. Our results delineate an inflammatory cascade of events occurring along disease progression within fibrovascular niches. It is initiated by endothelial dysfunction, followed by heme scavenging of CD163+ macrophages and production of CCL18. This chemokine synergizes with local CCL21 upregulation to influence the stromal composition favoring endothelial to mesenchymal transition.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 71 publications
(111 reference statements)
0
5
0
Order By: Relevance
“…We divided the COVID-19 cohort into acute and late cases according to disease duration (14 days post infection as cut-off; Supplementary Table 1 ) due to marked differences in lung pathology seen in these patients 20 . Therefore, we first performed post hoc principal component analysis (PCA) of the differentially expressed proteins in the different comparisons (acute vs. control and late vs. control) of the brainstem.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We divided the COVID-19 cohort into acute and late cases according to disease duration (14 days post infection as cut-off; Supplementary Table 1 ) due to marked differences in lung pathology seen in these patients 20 . Therefore, we first performed post hoc principal component analysis (PCA) of the differentially expressed proteins in the different comparisons (acute vs. control and late vs. control) of the brainstem.…”
Section: Resultsmentioning
confidence: 99%
“…We found CD4+ T cells but we also detected double positive (DP) CD4+ and CD8+ T cells in the perivascular space ( Figure 4 d ). DP T cells are a subpopulation known to accumulate in lung tissue of COVID-19 patients 20 and various other disorders 86 producing pro-inflammatory cytokines and displaying characteristics of memory CD8+ T lymphocytes 86 . Similar to blood derived T cells in severe COVID-19 85 , we identified T cells expressing granzyme B and PD-1, suggesting a still ongoing local (unconventional) activation within the perivascular space even in the late disease phase ( Figure 4 e ).…”
Section: Resultsmentioning
confidence: 99%
“…The lack of expression of CCL19 and CCL21 in PBMCs points to affected organs or associated lymphoid tissue as likely sources of increased circulating levels in our COVID-19 cohorts. Supporting a link between pulmonary CCL21 production and impaired lung function, a recent preprint report demonstrated the formation of perivascular foci with strong expression of CCL21 in lung tissue from patients with severe COVID-19 [ 38 ]. These areas showed high expression of fibrosis-associated markers, and accumulation of immune cell aggregates with features consistent with tertiary lymphoid structures.…”
Section: Discussionmentioning
confidence: 99%
“…These areas showed high expression of fibrosis-associated markers, and accumulation of immune cell aggregates with features consistent with tertiary lymphoid structures. CCL19 expression was also elevated in these areas [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the serum levels of CCL21 were found to be high in patients with COVID-19 who did not survive 12 days after SARS-CoV-2 infection [ 76 ]. Furthermore, human lung tissue sections from samples of patients with acute COVID-19 showed that CCL21 expression was weakly detectable but was upregulated in later phases of the disease, and the local expression of CCL21 recruited CCR7 + T cells and T follicular helper-like cells and can contribute to the formation of tertiary lymphoid structures in the lungs [ 77 ]. The precise role of CCL21 in the activation and impairment of proper T cells during SARS-CoV-2 infection remains unclear; thus, a subsequent study may define the precise role of this chemokine post-SASR-CoV-2 infection.…”
Section: Role Of Pulmonary Homeostatic Chemokines Cxcl13 Ccl19 and Cc...mentioning
confidence: 99%